Devastaciones ecosociales: ecología política y perspectivas críticas latinoamericanas - Andrea Lehner; Lina Álvarez Villareal; Nicolas Lema Habash (Revista de Estudios Sociales)
This introductory article to the thematic issue underscores the urgent need to address eco-social devastation through the social sciences, adopting a critical-political perspective that has been foundational to political ecology since its emergence. It argues that the Latin American perspective not only contributes significantly to this field by proposing transformative alternatives grounded in the everyday practices of historically marginalized communities, but also by forging connections between community-based practices and academia. Moreover, it is fostering a new epistemology and rationality centered on the Earth rather than on humankind. Following a brief contextualization of the central tenets of political ecology as a framework for understanding the interplay between environment and society, the article highlights the most significant contributions of Latin American political ecology. It examines how this perspective uniquely frames and interprets the eco-social devastations currently afflicting the region. Lastly, it introduces the specific contributions of the articles included in the dossier, emphasizing their anti-anthropocentric approach and the shared concept of critique that binds them together.